Experimental Study of Torque Using a Small Scoop on the Lunar Surface - Long Xue; Baichao Chen; Zhenjia Zhao; Zhaolong Dang; Meng Zou (International Journal of Aerospace Engineering)
Chinese missions to the moon are planned to sample the regolith and return it to the earth. Microscale excavators may be good candidates for these missions, as they would significantly reduce the launch mass. Thus, it is necessary to research the interaction between the scoop and the regolith being sampled. We present the development of a simple apparatus to measure excavation torque. All tests were conducted using TYII-2 regolith simulant with gravels. The test results show that, under loose regolith conditions, the penetrating angle and the bulk density had a great influence on the excavation torque, while the rotating speed had little effect. However, when the bulk density was compact, the rotating speed did influence the excavation torque. The excavation torque increased sharply when the scoop encountered the gravels; actually, some of the parameters will influence the value of the torque such as the diameter, quantity, and position and inbuilt depth of the gravels. When the excavation torque sharply increases, the operation should be immediately stopped and checked.